1988
DOI: 10.1902/jop.1988.59.12.823
|View full text |Cite
|
Sign up to set email alerts
|

Penetration and Uptake of Colloidal Gold‐Labeled Concanavalin A in The Junctional Epithelium of The Rat

Abstract: A complex of colloidal gold and concanavalin A (CG-Con A) with various biological properties and high ultrastructural resolution was applied into the sulcus of rat molar gingiva and traced with an electron microscope for three hours to examine the cytological changes occurring in the cells of the junctional epithelium (JE) during penetration of extrinsic irritants, and to determine the roles of JE cells in such a circumstance. While the penetration of CG-Con A was impeded on the surface of keratinized oral gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…6A), but only slightly. To explain this, it is reported that rat gingival junctional epithelium can uptake topically applied horseradish peroxidase or colloidal gold-labeled concanavalin A [24], [25]. Thus, the uptake of latex beads by BSA appears to have resulted from the intrinsic characteristics of epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…6A), but only slightly. To explain this, it is reported that rat gingival junctional epithelium can uptake topically applied horseradish peroxidase or colloidal gold-labeled concanavalin A [24], [25]. Thus, the uptake of latex beads by BSA appears to have resulted from the intrinsic characteristics of epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…The junctional epithelium has high permeability because of the presence of wide intercellular spaces. These spaces allow various substances to pass in and out of the epithelial layer, as demonstrated by experimental studies using tracers (15–17). From the standpoint of a defense system, however, this high permeability is a disadvantageous factor in periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Gometz et al (20) also reported that inflammatory macrophages resided preferentially immediately adjacent to the sulcular epithelia. It is well known that the permeability of JE allows entry of various substances (8,21). Some irritants in the oral environment can infiltrate into the gingival connective tissue through the wide intercellular space of JE in the normal condition.…”
Section: Discussionmentioning
confidence: 99%